Genomics of an emerging clone of Salmonella serovar Typhimurium ST313 from Nigeria and the Democratic Republic of Congo - Pimlapas Leekitcharoenphon; Carsten Friis; Ea Zankari; Christina Aaby Svendsen; Lance B. Price; Maral Rahmani; Ana Herrero-Fresno; Kayode Fashae; Olivier Vandenberg; Frank M. Aarestrup; Rene S. Hendriksen (Journal of Infection in Developing Countries)
Introduction: Salmonella enterica serovar Typhimurium ST313 is an invasive and phylogenetically distinct lineage present in sub-Saharan Africa. We report the presence of S. Typhimurium ST313 from patients in the Democratic Republic of Congo and Nigeria. Methodology: Eighteen S. Typhimurium ST313 isolates were characterized by antimicrobial susceptibility testing, pulsed-field gel electrophoresis (PFGE), and multilocus sequence typing (MLST). Additionally, six of the isolates were characterized by whole genome sequence typing (WGST). The presence of a putative virulence determinant was examined in 177 Salmonella isolates belonging to 57 different serovars. Results: All S. Typhimurium ST313 isolates harbored resistant genes encoded by blaTEM1b, catA1, strA/B, sul1, and dfrA1. Additionally, aac(6’)1aa gene was detected. Phylogenetic analyses revealed close genetic relationships among Congolese and Nigerian isolates from both blood and stool. Comparative genomic analyses identified a putative virulence fragment (ST313-TD) unique to S. Typhimurium ST313 and S. Dublin. Conclusion: We showed in a limited number of isolates that S. Typhimurium ST313 is a prevalent sequence-type causing gastrointestinal diseases and septicemia in patients from Nigeria and DRC. We found three distinct phylogenetic clusters based on the origin of isolation suggesting some spatial evolution. Comparative genomics showed an interesting putative virulence fragment (ST313-TD) unique to S. Typhimurium ST313 and invasive S. Dublin.